The Level Of Psychological Hardness Of A Sample Of Swimmers In Damascus Governorate - Mahmoud, Hala (Latakia University Journal -Medical Sciences Series, 2018)
The aim of the research is to identify the level of psychological hardness of a sample of swimmers in Damascus Governorate. Differences in the level of psychological hardness between the members of the research sample are defined according to the sex variables (males / females) and age (12/13/14/15) years. The sample consisted of (77) individuals divided into (54) males and (23) females. They were selected in a random stratified manner, where they applied a measure of psychological rigidity (prepared by the researcher) after verifying of validity and reliability. The results indicated that: There is an average level of psychological hardness in general among swimmers and members of the research sample in Damascus Governorate. There are statistically significant differences between the mean scores of the research sample on the psychological hardness scale according to gender variable in favor of males There are statistically significant differences between the mean scores of the individuals on the psychological rigidity scale according to the age variable for the benefit of the larger age. مستوى الصلابة النفسية لدى عينة من السباحين في محافظة دمشق هدف البحث التعرّف على مستوى الصلابة النفسية لدى عينة من السباحين في محافظة دمشق، والتعرف إلى الفروق في مستوى الصلابة النفسية بين أفراد عينة البحث وفقاً لمتغيري الجنس (ذكور/ إناث) والعمر (12/13/14/15) عاماً. وتكونت عينة البحث من (77) فرداً موزعين إلى (54) من الذكور، و(23) من الإناث. تم اختيارهم بالطريقة العشوائية الطبقية، حيث طُبقَ عليهم مقياس الصلابة النفسية (من إعداد الباحثة) بعد التحقق من صدقه وثباته. وأشارت النتائج إلى ما يلي: وجود مستوى متوسط من الصلابة النفسية بشكل عام لدى السباحين أفراد عينة البحث في محافظة دمشق. وجود فروق ذات دلالة إحصائية بين متوسط درجات أفراد عينة البحث على مقياس الصلابة النفسية تبعاً لمتغير الجنس لصالح الذكور. وجود فروق ذات دلالة إحصائية بين متوسط درجات أفراد عينة البحث على مقياس الصلابة النفسية تبعاً لمتغير العمر لصالح العمر الأكبر.